Scientific data governance and authorship policy in transdisciplinary research and innovation environmental projects (Revista Espinhaço, 2025)
Effective scientific data governance and equitable authorship attribution are essential to the success of large-scale, transdisciplinary research initiatives. Drawing on our experience in two major programmes, namely “Damage Diagnosis Programme following the Brumadinho dam disaster” in the Paraopeba River basin (PDD) and “IBI UHE-Furnas & UFMG” project, in the Grande River basin; each involving hundreds of investigators from academia, industry and civil society, we developed and implemented a comprehensive governance model. Core components include (1) field data collection with standardised protocols, which are curated to maintain consistency, reliability and reproducibility and (2) a structured authorship policy, which needs to be as objective as possible and guarantee fairness of credit among participants. We thus developed a policy based on the CRediT taxonomy, where we require least four contributorship roles (including writing as a mandatory one) for authorship and offering co-authorship eligibility to those meeting four roles; and a diverse Scientific Committee to oversee proposal review, manage conflicts of interest and prevent redundant research. All manuscripts must undergo centralised submission and use only validated datasets, while acknowledgements and compliance statements align with relevant data-protection and ethical regulations. Implementation of this framework has clarified contributor roles, mitigated gift and ghost authorship, fostered transparent workload distribution and enhanced inclusivity, particularly for early-career and under-represented researchers. Our findings demonstrate that a deliberately flexible yet rigorous governance-and-authorship policy can balance autonomy, fairness and accountability. This model provides a replicable blueprint for other large, collaborative research programmes seeking to fairly uphold integrity, promote diversity and accelerate trustworthy scientific discovery.
Keywords: scientific writing; scientific publication; ethics; research; innovation; compliance